2017
DOI: 10.1017/s0022149x17000736
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic characterization ofPterygodermatites(Paucipectines)zygodontomis(Nematoda: Rictulariidae) fromNecromys lasiurus(Rodentia: Sigmodontinae) from Uberlândia, Brazil

Abstract: Pterygodermatites (Paucipectines) zygodontomis, a nematode parasite of the small intestine of the rodent Necromys lasiurus, from Uberlândia, Minas Gerais state, Brazil, was analysed by light and scanning electron microscopy. Additionally, phylogenies were inferred from the mitochondrially encoded cytochrome c oxidase I gene (MT-CO1). Details of the helminth surface, such as the oral aperture, cephalic papillae, papillae in the posterior region of the body and longitudinal cuticular elements represented by spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Among the helminths described in N. lasiurus , nematodes are the most frequently reported (Vicente et al ., 1997; Anderson et al ., 2009). In general, studies of helminths from Brazilian rodents often reported nematodes (Vicente et al ., 1997; Anderson et al ., 2009; Simões et al ., 2010, 2011, 2012, 2017; Cardoso et al ., 2016; Tavares et al ., 2017; Costa et al ., 2018); however, most studies are case reports. Studies of acanthocephalans from rodents, including taxonomy, ecology, molecular biology and phylogeny, are still scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the helminths described in N. lasiurus , nematodes are the most frequently reported (Vicente et al ., 1997; Anderson et al ., 2009). In general, studies of helminths from Brazilian rodents often reported nematodes (Vicente et al ., 1997; Anderson et al ., 2009; Simões et al ., 2010, 2011, 2012, 2017; Cardoso et al ., 2016; Tavares et al ., 2017; Costa et al ., 2018); however, most studies are case reports. Studies of acanthocephalans from rodents, including taxonomy, ecology, molecular biology and phylogeny, are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…During an investigation of hantavirus cases (Limongi et al , 2013), rodents were captured in the municipality of Uberlândia (18°55'07″S, 48°17'19″W), in the state of Minas Gerais, south-eastern Brazil, within the Cerrado biome. Helminths were recovered for an ecological study of the metacommunity structure of the helminth community of the rodent N. lasiurus (Costa et al ., 2018). From that study, we recovered specimens of the genus Moniliformis , which had never been previously reported for this host.…”
Section: Introductionmentioning
confidence: 99%
“…zygodontomis, Grossmann (2015) reported higher prevalence, abundance, and intensity in N. lasiurus than in the present study. This species was reported in Rhipidomys mastacalis, also in Uberlˆandia (Cardoso, 2016;Costa et al, 2017). Quentin (1967) reported this species in N. lasiurus and in Ca.…”
Section: Helminths Species and New Recordsmentioning
confidence: 76%
“…to GenBank (accession number: KY462830.1). The latter sequence obtained from a specimen isolated from Mastomys coucha in South Africa is nearly identical (99%) to a partial (631 bp) 18S sequence of P. muricola (KP760162) from a gorilla of Central African Republic, but has a sequence identity of only 95% to P. numidica (KT894812, KT894811) not included for our analysis due to its controversial morphological assignment (Costa et al 2018 ).
Fig.
…”
Section: Resultsmentioning
confidence: 97%
“…The sequences from P. muricola built a separate group with CO1 sequence identities of 84.99–85.62% (472 bp) to Mastophorus from Mus . Misidentifications, erroneously assigned sequences like those from P. numidica sequences obtained from specimens collected from Oxymycterus in Brazil (de Barros 2015 ) assigned to the genus Prostospirura without describing details or illustrating their specimens, while belonging to the genus Mastophorus (Costa et al 2018 , 2022 ), are challenging to conclude and might promote confusion in the classification. While further studies should focus on data generation, validation (by associated taxonomic annotation) and phylogenetic analysis of reference sequences to clarify the confusion of Mastophorus with Protospirura , our work provides a deeper insight into the morphological and phylogenetic diversity of the genus Mastophorus.…”
Section: Discussionmentioning
confidence: 99%